2020
DOI: 10.1002/jcla.23093
|View full text |Cite
|
Sign up to set email alerts
|

Plasma level of miR‐99b may serve as potential diagnostic and short‐term prognostic markers in patients with acute cerebral infarction

Abstract: Objective The aim of the present study is to explore the potential diagnostic and prognostic value of plasma levels of miR‐99 family for patients with acute cerebral infarction (ACI). Methods A total of 112 patients who have been diagnosed with ACI were enrolled in this study, and 112 healthy volunteers were served as the controls. The plasma of the patients and controls were collected, and total RNAs were isolated, and the expression levels of miR‐99a, miR‐99b, and miR‐100 in the plasma of patients and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Patients with CI will suffer varying degrees of damage to their cognitive function (CF) and activities of daily living (ADL) due to the development of the disease, which will impose heavy economic and psychological burden to patients and their families [ 5 ]. Previous studies have shown that CI can lead to severe sequelae and even disability and death if optimal clinical decisions are not made promptly [ 6 ]. Therefore, designing a more effective and reliable treatment scheme for CI is of great significance for reducing the high mortality, disability, and recurrence rates of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CI will suffer varying degrees of damage to their cognitive function (CF) and activities of daily living (ADL) due to the development of the disease, which will impose heavy economic and psychological burden to patients and their families [ 5 ]. Previous studies have shown that CI can lead to severe sequelae and even disability and death if optimal clinical decisions are not made promptly [ 6 ]. Therefore, designing a more effective and reliable treatment scheme for CI is of great significance for reducing the high mortality, disability, and recurrence rates of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…1 Without rapid clinical decision-making, ACI may result in severe outcomes, such as disability or even death; consequently, early diagnosis of ACI is crucial for the improvement of curative effects and the reduction of potential sequelae and mortality. 2 Currently, ACI diagnosis mainly relies on neuroimaging techniques, such as magnetic resonance imaging (MRI) and computed tomography (CT), nevertheless, the availability of this expensive device is restricted and image interpretation may be inconsistent in the early stage of stroke, which limits the efficiency of decision-making in ACI. 3 The lack of rapid and effective clinical decision-making in ACI could result in serious consequences.…”
Section: Introductionmentioning
confidence: 99%
“…6 Accumulating studies have unveiled the aberrant expression of miRNAs in the brain tissues and peripheral blood of ACI patients, implying that miRNAs are implicated in the pathogenesis, diagnosis, and prognosis of ACI. 2,7,8 miR-124 is identified as one of the most abundant miRNAs in the human brain that modulates variant biological functions of the central nervous system (CNS), and dysregulated miR-124 is tightly associated with stroke. 9 The elevated miR-124 expression has the property to reduce the infarct size and facilitate the recovery of neurological functions post-ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…21 Increasing evidence suggests that circulating microRNAs may be potential biomarkers for the diagnosis of ACI. [21][22][23] For instance, miR-124 levels are shown to be reduced in ACI patients and the dynamic changes of miR-124 may be useful for the monitor of ischemic stroke. 24 In the present study, we found that the expression of plasma miR-409-3p in the ACI group was higher than that in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…ACI is a major cause of death and an important contributor to brain‐related mortality worldwide 21 . Increasing evidence suggests that circulating microRNAs may be potential biomarkers for the diagnosis of ACI 21–23 . For instance, miR‐124 levels are shown to be reduced in ACI patients and the dynamic changes of miR‐124 may be useful for the monitor of ischemic stroke 24 …”
Section: Discussionmentioning
confidence: 99%